Financial literacy, behaviour and well-being of millennials in Poland compared to previous generations: The insights from three large-scale surveys - Andrze Cwynar (Review of Economic Perspectives, 2020)
There are many concerns about financial competences of Millennials. Initial research on this generation suggests that it is less financially knowledgeable and exhibits less healthy financial behaviours compared to other generations. The goal of the article is to compare Millennials to non-Millennials as a whole, as well as to other generations treated in isolation, to check whether Millennials diverge in terms of financial literacy, behaviour and well-being. To that end, this study uses three distinct datasets from three surveys conducted in 2017 and 2018 on different samples of Poles. The applied statistic tests of significant differences do not confirm that Millennials diverge from other generations with respect to financial literacy as well as behaviours related to cash management, saving and investment. However, the surveyed Millennials perform significantly less healthy credit management and insurance behaviours compared to non-Millennials. We also found that Millennials report significantly higher levels of financial well-being compared to all previous generations.
Keywords: D14; D15; G51; G53; 330; financial literacy; debt literacy; financial behaviour; financial well-being; Millennials